Amplifying climate crisis through timelines: Digital activism of XR Indonesia and FFF Indonesia - Ayu Kartika; Mondry; Arkhan Naufal; Romi Arifin (C-DISC, 2026)
The rapid development of Information and Communication Technology (ICT) has transformed various dimensions of social life, including climate activism. In Indonesia, where internet penetration reached 79.5% in 2024, social media has become a strategic platform for environmental advocacy. This study examines the online climate change campaigns of Extinction Rebellion Indonesia and Fridays for Future Indonesia on Instagram, the primary platform for their digital activism. Employing a descriptive qualitative approach, data were collected through in-depth interviews with five key informants from both organizations and qualitative content analysis of their Instagram posts published between February and September 2024. The findings reveal that the two organizations adopt distinct yet complementary campaign strategies. Extinction Rebellion Indonesia reinforces the climate emergency narrative through the integrated use of images, videos, text, and strategic hashtags. In contrast, Fridays for Future Indonesia employs a more accessible approach by presenting climate issues through simple, engaging, youth-oriented content, including memes, trending topics, and personalized messages. The study concludes that digital platforms enable climate movements to construct collective narratives, amplify climate crisis discourse, strengthen collective identities, and foster broader public engagement.